Clipping Lists and Change Borders: Improving Multitasking Efficiency with Peripheral Information Design - Matthews, Tara; Czerwinski, Mary; Robertson, George; Tan, Desney (CHI 2006 Conference on Human Factors in Computing Systems, 2006)
Information workers often have to balance many tasks and interruptions. In this work, we explore peripheral display techniques that improve multitasking efficiency by helping users maintain task flow, know when to resume tasks, and more easily reacquire tasks. Specifically, we compare two types of abstraction that provide different task information: semantic content extraction, which displays only the most relevant content in a window, and change detection, which signals when a change has occurred in a window (all designed as modifications to Scalable Fabric [17]). Results from our user study suggest that semantic content extraction improves multitasking performance more so than either change detection or our base case of scaling. Results also show that semantic content extraction provides significant benefits to task flow, resumption timing, and reacquisition. We discuss the implication of these findings on the design of peripheral interfaces that support multitasking.